Contextual consistency promotes visual-haptic simultaneity perception - Umemura, Hiroyuki; Iwaki, Sunao (Frontiers in Human Neuroscience, 2025)
In this study, we investigate the influence of causality validity in the information provided to each of two sensory modalities on the integration of multisensory information. For the purpose, stimuli that simulated a causal event, a ball striking an object, were created using a head-mounted display and a haptic device. The visual position and motion of the object were aligned to the haptic feedback received by the observer. The haptic device delivered a vibration around the moment of impact. Three vibration directions were used to assess the effect of the validity of the causal relationship between the two events. Participants were asked to determine whether the collision of the ball and the vibration were simultaneous. The findings revealed that the participants were more likely to perceive the events as simultaneous when the direction of the vibration matched the ball’s movement. These results suggest that valid causal consistency across different modalities enhances the binding of these signals as originating from a single source.